The coordinated operation strategy of multi-type power generations in different modes in prosumer with high renewables - Hu, Xuekai; Meng, Liang; Su, Can (Frontiers in Energy Research, 2023)
The renewable energy with distributed generation is widely used because of the cleanliness and sustainability. However, when high renewables connect to the grid, the randomness and intermittent of the renewable energy will deteriorate the performance. As the important interface between distributed generations and power grid, the prosumer can contribute to the improvement of the renewable energy penetration if stable and reliable operation of the power supply is realized. The prosumer has multi-type generations, loads and auxiliary converters, where the characteristics interact each other. Moreover, due to the complicated grid states, the prosumer may operate in different conditions. Therefore, the research on the coordinated operation control strategy of the multiple electrical facilities is necessary in the prosumer with high renewables. In this paper, the AC/DC hybrid prosumer is established with multi-type distributed generations, loads and auxiliary converters. The prosumer can operate in normal grid-connected mode and grid-fluctuation mode. In different modes, the cooperation control of the power converter in the prosumer is proposed, which changes according to the grid demands. When over-limited grid voltage and frequency fluctuation are detected in the point of common coupling, the prosumer can switch from normal grid-connected mode to grid-fluctuation mode to provide voltage and frequency support. Finally, the simulation results based on Matlab/Simulink is employed to verify the effectiveness of the proposed control strategy.